Active factor XI is associated with the risk of cardiovascular events in stable coronary artery disease patients. (April 2022) - Paszek, Elżbieta; Pociask, Elżbieta; Ząbczyk, Michał; Piórkowski, Adam; Butenas, Saulius; Legutko, Jacek; Undas, Anetta
Abstract: Background and aims: Tissue factor (TF) and activated factor XI (FXIa) have been associated with acute coronary syndrome, ischemic stroke and venous thromboembolism. Their predictive value in stable coronary artery disease (CAD) is unclear. We investigated whether active TF and FXIa were associated with clinical outcomes in CAD patients in long-term observation. Methods: In 124 stable patients with multivessel CAD, we assessed the presence of circulating, active TF and FXIa by measuring a response of thrombin generation to respective inhibitory antibodies. We recorded the composite endpoint of myocardial infarction (MI), stroke, systemic thromboembolism and cardiovascular death during follow-up (median 106 months, interquartile range 95–119). Results: Circulating FXIa and active TF were detected in 40% and 20.8% of the 120 patients (aged 65.0 [57.0–70.3] years, men, 78.3%), who completed follow-up. The composite endpoint occurred more frequently in patients with detectable active TF and FXIa present at baseline (hazard ratio [HR] 4.02, 95% confidence interval [CI] 2.26–7.17, p < 0.001 and HR 6.21, 95% CI 3.40–11.40, p < 0.001, respectively). On multivariate analysis FXIa, but not active TF, was an independent predictor of the composite endpoint, as well as MI, stroke/systemic thromboembolism, and cardiovascular death, when analyzed separately. Conclusions: To our knowledge, this study is the first to show that circulating FXIa predicts arterial thromboembolic events in advanced CAD, supporting a growing interest in FXIa inhibitors as novel antithrombotic agents. Graphical abstract: Image 1 Highlights: The prognostic role of active tissue factor (TF) and activated FXI (FXIa) in coronary artery disease (CAD) is unclear. We investigated the impact of active TF and FXIa on long-term outcomes in CAD patients. FXIa and, to a lesser extent, active TF were associated with cardiovascular events in CAD. Targeting FXIa might represent a promising preventive strategy in high-risk CAD patients.